Differences in some variables that estimate obesity between 12 year olds from the city and the suburbs - Shukova-Stojmanovska D.; Georgiev G.; Gontarev S. (Faculty of physical education, sport and health, 2017)
This research was implemented on a population of 93 male, 11 years old, sixth grade in two elementary schools from Skopje: “11 Oktomvri”(downtown) and “Aco Shopov”(in Radishani, as a suburb). The purpose was to determine the differences in some variables that estimate obesity between pupils that live in center and in suburb. 8 variables were measured: body mass (BM), height (BH), body mass index (BMI), height (PBH) and body mass index (BMI), percent of fat tissue (Fat%), abdominal (abdsf), back (backsf) and upper arm (uparmsf) skin folds and an index for estimating obesity as a sum of body mass index and three skin fold thicknesses (BMI+sum). Besides the expectations that differences will appear due to the settlement where pupils live, however such differences are not present between male pupils. There might be several reasons for such condition, maybe physical inactivity in pupils that live in both settlements, inappropriate nutrition and mixing the pupils that live and go to school in center, with pupils that only learn in that school, and live in other settlement.
Keywords: 12 years old pupils, male, female, obesity, center, suburb